FAMILY BURDEN AND RELAPSE PREVENTION AMONG PATIENTS WITH SCHIZOPHRENIA: A CROSS-SECTIONAL STUDY - Jihan Rabial; Riski Dian Ardianti (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Family burden can affect the continuity of community-based care for people with schizophrenia, particularly medication supervision, recognition of early warning signs, and access to mental health services. This study examined the association between family burden and relapse-prevention practices among patients with schizophrenia in the working area of Puskesmas Juli-2, Bireuen Regency. An analytic cross-sectional study was conducted among 58 primary family caregivers selected purposively from 137 registered families. Data were collected on 1-7 July 2024 using a 12-item family-burden questionnaire adapted from Manao and Pardede and a 20-item relapse-prevention questionnaire. Data were summarized descriptively, and the association was tested using a chi-square procedure with Fisher-Freeman-Halton exact significance at α = 0.05. Most families had moderate burden (56.9%), and most reported good relapse prevention (62.1%). Good prevention was reported by 94.7% of families with light burden, 54.5% with moderate burden, and none with heavy burden. Family burden was significantly associated with relapse prevention (p < 0.001; Cramer's V = 0.576). Families with heavier burden require prioritized education, stress-management support, medication-access facilitation, and home-based follow-up.